PELAKSANAAN REHABILITAS AC – WC PADA RUAS JALAN DI KOMPLEK SRI MULYONO TNI AU LANUD PALEMBANG - Muchlisin, Muchlisin; Firdaus, Firdaus (Ensiklopedia of Journal, 2024)
A road is a facility created to facilitate transportation by land and plays a major role in the technology and development of a region. The increase in economic activity in a region from year to year cannot be separated from the availability of facilities and infrastructure on one of the roads in the SRI MULYONO TNI AU base complex. HERBAL SYMBOLS . In the city of Palembang, road facilities and infrastructure often become damaged over time. Sometimes this increase in traffic volume is not accompanied by an increase in road capacity. Therefore, efficient transportation services are needed as one of the land transportation infrastructure, the most important of which is roads as connecting access between one place and another so that it is easier to reach. Road infrastructure development aims to facilitate the flow of distribution of goods and services, as well as play a role in improving the quality of life and human welfare. To restore the service condition of this road, road maintenance is needed. One type of road maintenance is road improvement. Road improvements can take the form of improving the road pavement structure and also widening the road to increase road capacity.Keywords: Implementation of rehabilitation and improvement of road sections